Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1029/2019jd031411
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of CloudSat's Cloud‐Profiling Radar for Mapping Snowfall Rates Across the Greenland Ice Sheet

Abstract: The Greenland Ice Sheet is now the single largest cryospheric contributor to global sea‐level rise yet uncertainty remains about its future contribution due to complex interactions between increasing snowfall and surface melt. Reducing uncertainty in future snowfall predictions requires sophisticated, physically based climate models evaluated with present‐day observations. The accuracy of modeled snowfall rates, however, has yet to be systematically assessed because observations are sparse. Here, we produce hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…CloudSat is one of the few precipitation radar satellites that samples snowfall poleward of 60°N. However, CloudSat cannot resolve snowfall rates below 1,200 m above the surface due to ground clutter (Palerme et al., 2019; Ryan et al., 2020). Furthermore, its sparse spatiotemporal sampling requires retrievals to be aggregated onto coarse grids that also likely introduces uncertainty (Bennartz et al., 2019; Ryan et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CloudSat is one of the few precipitation radar satellites that samples snowfall poleward of 60°N. However, CloudSat cannot resolve snowfall rates below 1,200 m above the surface due to ground clutter (Palerme et al., 2019; Ryan et al., 2020). Furthermore, its sparse spatiotemporal sampling requires retrievals to be aggregated onto coarse grids that also likely introduces uncertainty (Bennartz et al., 2019; Ryan et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, CloudSat cannot resolve snowfall rates below 1,200 m above the surface due to ground clutter (Palerme et al., 2019; Ryan et al., 2020). Furthermore, its sparse spatiotemporal sampling requires retrievals to be aggregated onto coarse grids that also likely introduces uncertainty (Bennartz et al., 2019; Ryan et al., 2020). Discrepancies between modeled and remotely sensed snowfall rates therefore remain mostly unresolved and will continue to be without expansion of the currently sparse network of in situ stations.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the S/P ratio derived from the satellite data is still physically meaningful. There are a few studies in the literature on comparing CloudSat snowfall product with surface station measurements [52][53][54], ground-based radar measurements [55][56][57][58], and model reanalysis [59][60][61]. Most of these studies are conducted over high latitudes.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, King [53] evaluated CloudSat snowfall product against four station measurements and three gridded snow water equivalent products throughout the Canadian Arctic and found that CloudSat has better performance north of 70 • N, with underestimation compared to measurements at most of the stations and the reanalysis. Ryan et al [61] derived a 15-km resolution snowfall climatology from CloudSat snowfall retrievals over Greenland ice sheet and concluded that CloudSat accumulation climatology has an uncertainty of ± 28% with respect to accumulation rates derived from ice cores. Edel et al [60] compared CloudSat snowfall climatology with several reanalysis datasets and found that similar general geographical patterns are observed in all datasets, although there are significant mean snowfall rate differences over the Arctic between 58 • and 82 • N. Using conventional surface weather station data over Canada, Hiley et al [52] found that CloudSat snowfall retrieval does not correlate well with surface station measurements, except for at some high latitude stations where CloudSat has more frequent sampling and mixed phase precipitation is less of an issue.…”
Section: Discussionmentioning
confidence: 99%
“…With their frequent coverage over high-latitudes and wide scan swath, high-frequency (e.g., frequencies above~90 GHz) passive MW sensor-based precipitation data have significant potential to provide estimates where cold-season precipitation (i.e., precipitation reaching the surface in its solid phase, and also drizzle and sleet) is an important contribu-tion to total annual precipitation [19][20][21][22][23]. In this section, several recent investigations are highlighted whereby the CloudSat-GPM coincidence dataset is used to validate passive MW-based precipitation estimates, as well as to exploit the three-frequency radar data to address limitations of individual radar retrievals of cold-season precipitation [24].…”
Section: Applications To Cold-season Precipitationmentioning
confidence: 99%